SELEKTIVITAS KERJA, PERSEPSI PEKERJAAN FORMAL TERHADAP PEROLEHAN KESEMPATAN KERJA - Walujo Sedjati, Hari (Paradigma: Jurnal Masalah Sosial, Politik, dan Kebijakan, 2019)
In general functional proverty was found to be related to unployment in Kangannyar subdistrict; Purbalingga district; Central Java Province. The research analyses two antecedent (Independet variables) : Selectivity work ; Perseption formal work and one main consequent (Dependent variable) : a getting work. The reseach find out selectivity work positive correlation and significant (0,262), to getting work. The perseption formal work positive corelation and significant ( 0,238) with getting work. Coefisient Of Determinant find out, R 3.12= 0,6051. All together degree selectivity work, and perseption formal work influences dificult get work 60,51 %, so that mosf of work force unployment. In spite of great heterogeneity among the less developed countries, they have certain common characteristics and problems, Less developed countries are generally typified by a relatively low per capita income, low productivity per son, and high birth influence large unemployment